x+y=-6
x*y=-7
Nu imi pot da seama cum sa fac.
Răspunsuri la întrebare
Răspuns de
0
x + y = -6=> x= -6-y
x×y =-7=>(-6-y )×y=-7
-6y- y^2 +7=0
∆=(-6)^2-4×(-1)×7
∆=36+28
∆=64
x1=( -6-√64 ) ÷2
x1=( -6-8 )÷2=-14÷2=-7
x2=(-6+√64 )÷2
x2=(-6 +8) ÷2=2÷2=1
x×y =-7=>(-6-y )×y=-7
-6y- y^2 +7=0
∆=(-6)^2-4×(-1)×7
∆=36+28
∆=64
x1=( -6-√64 ) ÷2
x1=( -6-8 )÷2=-14÷2=-7
x2=(-6+√64 )÷2
x2=(-6 +8) ÷2=2÷2=1
balalala2:
fata cat e xcat e y?
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă